Habitat preferences and seasonal activity of the Microstigmatidae from Ngome State Forest, South Africa (Arachnida: Araneae) - A.S. Dippenaar-Schoeman; M. van der Merwe; A.M. van den Berg (Koedoe: African Protected Area Conservation and Science, 2006)
As part of the South African National Survey of Arachnida (SANSA) inventories are underway to determine the arachnid biodiversity of various biomes. Asurvey of groundliving spiders was conducted over a year period (1992-1993) at Ngome State Forest, KwaZulu-Natal, South Africa. Spiders were collected with 180 pitfall traps from five different habitat types ranging from indigenous forest to a pine plantation and grassland. A total of 186 specimens of the rare Mygalomorphae family Microstigmatidae were sampled, representing 2 % of the total spider fauna collected during the study. Two species, Microstigmata longipes (Lawrence) and M. zuluensis (Lawrence), occur sympatrically. Both species were more active in the indigenous forest, and were absent or present in low numbers in the open grass and pine plantation. Microstigmata zuluensis was slightly more abundant (59 % of total) and was recorded from three of the five habitats, while M. longipes (41 %) was found in four of the habitat types. Both species were active throughout the year with the lowest numbers recorded in winter (June to August). The males of M. longipes peaked in November while those of M. zuluensis peaked in April.